2016
DOI: 10.1111/1365-2656.12582
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific interference competition at the resource patch scale: do large herbivores spatially avoid elephants while accessing water?

Abstract: Animals may anticipate and try to avoid, at some costs, physical encounters with other competitors. This may ultimately impact their foraging distribution and intake rates. Such cryptic interference competition is difficult to measure in the field, and extremely little is known at the interspecific level. We tested the hypothesis that smaller species avoid larger ones because of potential costs of interference competition and hence expected them to segregate from larger competitors at the scale of a resource p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Thus, competition for a limited resource, such as water in dry times, can lead to high niche overlap (Gotelli & Ellison, 2013) and not the low niche overlap expected for species that can coexist by partitioning their resources (Connell, 1980). Similarly, Ferry et al, (2016) found that smaller herbivores spatially avoided elephants at the beginning of the dry season, but not later, even though elephant usage of waterholes increased as the dry season progressed.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, competition for a limited resource, such as water in dry times, can lead to high niche overlap (Gotelli & Ellison, 2013) and not the low niche overlap expected for species that can coexist by partitioning their resources (Connell, 1980). Similarly, Ferry et al, (2016) found that smaller herbivores spatially avoided elephants at the beginning of the dry season, but not later, even though elephant usage of waterholes increased as the dry season progressed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Valeix et al (2007) showed a temporal avoidance of African elephants Loxodonta africana by several other herbivores species. However, a recent study revealed that when zebras Equus quagga, and to a lesser extent kudus Tragelaphus strepsiceros, co-occur with elephants around pumped waterholes at the end of the dry season, they tend to all aggregate in the same specific sections of the waterhole area (Ferry et al 2016). One hypothesis suggested to explain this unexpected result is that it is not only the presence or the quantity of the resource that matters but its quality.…”
Section: Introductionmentioning
confidence: 99%
“…Animal conflicts are common across many taxa (e.g., Bonacci et al, 2006; Ferry et al, 2016; Robins, 2008; Robinson, 2014; Souza, Ilarri & Rosa, 2011; Tierney, Godleski & Massanari, 2000) and can be either inter or intraspecifically orientated. Bouts over food resources and territorial disputes are common inter and intraspecific interactions (e.g., Dröscher & Kappeler, 2014; Souza, Ilarri & Rosa, 2011), while disputes for mates, protection of offspring and social hierarchy inside a given population are exclusive intraspecific interactions (e.g., Lee, Yang & Curley, 2018; Sato & Nagayama, 2012; Souza & Ilarri, 2014).…”
Section: Introductionmentioning
confidence: 99%